ANALYSIS OF DIGITAL READINESS AND TPACK OF PGSD STUDENTS IN FACING THE DIGITAL TRANSFORMATION OF BASIC EDUCATION - Eko Purnomo; Fauzia Harun; Wawan S. Nadra; Rasmi Hi Panu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Digital transformation in basic education requires prospective teachers to possess adequate digital readiness and Technological Pedagogical Content Knowledge (TPACK) competence. This study aims to analyze the level of digital readiness and TPACK competence of students in the Primary School Teacher Education (PGSD) Program in facing the digital transformation of basic education. This study employs a descriptive quantitative approach using a survey method. Data were collected from 95 PGSD students through digital readiness and TPACK questionnaires using a five-point Likert scale. Data analysis was conducted descriptively, including mean, median, standard deviation, percentage, and categorization into low, medium, and high levels. The results show that students’ digital readiness is in the high category (M = 4.04), while TPACK competence is also in the high category (M = 3.81). Dimensional analysis indicates that students have good mastery of access and basic digital skills, but the pedagogical integration of technology in learning still needs to be strengthened. These findings indicate that PGSD students are generally ready to face digital transformation; however, strengthening integrative TPACK-based learning is still highly necessary in teacher education programs.